Comparison of the Frequency of Wound Infection in Patients Undergoing Toilet Mastectomy Versus Simple Mastectomy in Patients with Fungating Breast Tumor at Tertiary Care Hospital, Karachi - Manal; Prinka; Ali, Rashid; Afridi, Hamra; Wakil, Rafia; Ali, Mansab (Indus Journal of Bioscience Research, 2025)
Background: Fungating breast tumors often require palliative surgical intervention. However, the optimal approach for minimizing postoperative wound infection remains unclear. This study compared the frequency of wound infections following toilet mastectomy and simple mastectomy in patients treated at a tertiary care hospital. Methods: This randomized controlled trial was conducted in the Department of Surgery at JPMC, Karachi, over a period of six months. We enrolled 68 patients with fungating breast tumors and assigned them to one of two surgical groups. One group was toilet mastectomy (Group A) and the other groups was simple mastectomy (Group B). We documented wound infections postoperatively and examined associations with age, education, income, and occupational status. Results: Group A had a lower rate of wound infection (14.7%) compared to Group B (41.2%). Although the difference did not reach statistical significance (p = 0.15). Patients with lower education levels and those who were employed showed a slightly higher infection rate across both groups, but these patterns were not statistically significant. Conclusion: Toilet mastectomy appeared to reduce the frequency of wound infection rates compared to simple mastectomy in patients with fungating breast tumors.